THE ROLE OF TEACHERS AND SCHOOL CULTURE IN SHAPING GRADUATE QUALITY AT SDN 006 BATU BELAH - Riza Diliyawati; Nunu Mahnun (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Graduate quality is a key indicator of educational success, especially at the primary level where academic, character, and social development are formed. This study aims to analyze the role of teachers’ pedagogical competence and school culture in shaping graduate quality at SDN 006 Batu Belah. A qualitative case study approach was used to gain an in-depth understanding of the phenomenon. The participants included one principal, six teachers, and ten students selected through purposive sampling. Data were collected through interviews, observations, and documentation, and analyzed using interactive techniques involving data reduction, data display, and conclusion drawing. The findings indicate that teachers’ pedagogical competence significantly enhances student engagement and learning outcomes through effective planning, implementation, and evaluation. School culture, reflected in discipline, character values, and daily habits, also contributes to a conducive learning environment. However, collaboration within the school culture still needs improvement. The study further reveals that the synergy between pedagogical competence and school culture has a stronger impact on graduate quality than either factor alone. Therefore, improving graduate quality requires an integrated approach that strengthens both aspects simultaneously.